Evaluation Of The Implementation Of The Government Internal Control System (Spip) At The Central Papua Provincial Inspectorate - Triatmi Pujiastuti; Yoel Pasae; Since Erna Lamba (Jurnal Inovasi Global, 2025)
This research investigates and analyzes the Evaluation of the Implementation of the Government Internal Control System (SPIP) in the Inspectorate of Central Papua Province. The research object is the Inspectorate of Central Papua Province. The data sources include primary and secondary data. The data collection methods used are observation, interviews, and documentation. This study involves 11 employees from the Inspectorate of Central Papua Province. The data analysis technique employs qualitative descriptive analysis, beginning with data reduction, proceeding to data presentation, and concluding. The study concludes that: 1) The implementation of the Government's Internal Control System (SPIP) in the Inspectorate of Central Papua Province is a crucial step in ensuring that regional finances and assets are managed effectively, transparently, and in an accountable manner. 2) The implementation of the Government Internal Control System (SPIP) in the Inspectorate of Central Papua Province faces various significant challenges, including limitations in human resources, inadequate infrastructure, resistance to change, and dependence on external resources. 3) The effectiveness of the Government Internal Control System (SPIP) training in the Inspectorate of Central Papua Province can be measured through the increased understanding of employees, consistent policy implementation, and audit results indicating improvements in financial management